Electromyography normalization methods for high-velocity muscle actions: Review and recommendations - Ball, B.; Scurr, J. (Journal of Applied Biomechanics, 2013)
Electromyograms used to assess neuromuscular demand during high-velocity tasks require normalization to aid interpretation. This paper posits that, to date, methodological approaches to normalization have been ineffective and have limited the application of electromyography (EMG). There is minimal investigation seeking alternative normalization methods, which must be corrected to improve EMG application in sports. It is recognized that differing normalization methods will prevent cross-study comparisons. Users of EMG should aim to identify normalization methods that provide good reliability and a representative measure of muscle activation. The shortcomings of current normalization methods in high-velocity muscle actions assessment are evident. Advances in assessing alternate normalization methods have been done in cycling and sprinting. It is advised that when normalizing high-intensity muscle actions, isometric methods are used with caution and a dynamic alternative, where the muscle action is similar to that of the task is preferred. It is recognized that optimal normalization methods may be muscle and task dependent.